Innovative High-Speed Homogenizer Approach for Synthesizing PVDF-GO Membranes from Recycled Battery Graphite - Febriasari, Arifina; Ferdiansyah, Ferry; Salsabila, Shafa Marwa; Ridwan, Muhammad; Mahardika, Muhammad Bagas Adhistya; Hilyati, Hilyati; Sudjarwo, Wisnu Arfian Anditya; Arlofa, Nina; Supriyadi, Supriyadi; Toca-Herrera, Jose Luis; Kartohardjono, Sutrasno (Indonesian Journal of Chemistry, 2025)
Effective waste management is essential for achieving a zero-waste environment, particularly in handling hazardous domestic waste like used dry cell batteries. This study explores a sustainable approach by recovering graphite from battery waste to synthesize graphene oxide (GO) for enhancing poly-vinylidene fluoride (PVDF) membranes. GO was synthesized using the Hummers method and a modified high-speed homogenization approach, then characterized via Raman spectroscopy and X-ray diffraction (XRD). The fabricated PVDF-GO membranes were further analyzed using SEM-EDS, AFM, water contact angle measurements, and bacterial rejection tests. Results confirmed successful GO synthesis and integration into the polymer matrix. GO incorporation improved hydrophilicity, reducing the water contact angle from 120° (pure PVDF) to 66° and 56° in PVDF/PVP-GO membranes via high-speed homogenization and conventional methods, respectively. The modified membranes exhibited a 5–6 times larger pore size than pure PVDF and achieved nearly 100% bacterial rejection. Additionally, PVDF/PVP-GO(h) showed a 91.76% faster production time efficiency than PVDF/PVP-GO(s).